Edukasi Financial Ilegal Dalam Bentuk Pinjaman Online dan Investasi Online Berdasarkan Penilaian Otoritas Jasa Keuangan (OJK) Pada Koperasi Kelompok Wanita Tani “Melati Jaya” Kelurahan Sukamenanti Baaru Kecamatan Kedaton Kota Bandar Lampung - Wulan, Mutiasari Nur; Dalimunthe, Nindytia Puspitasari; Rusman, Tedi; Nurdin, Nurdin (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Currently, Fintech does not only enter Banking Financial Institutions, but also Non-Bank Financial Institutions. This can be seen in Financial Technology products circulating on social media, namely online loans and online investments. This condition actually provides convenience to the community, but there is also a negative impact, namely people who are trapped in online loans and online investments. There are many findings of online loan products and illegal online investments, this creates unrest in the community. Therefore, there is a need for education regarding illegal online loans and illegal online investments in collaboration with the Financial Services Authority (OJK) so that the public, especially mothers, are more careful in choosing to use online loan services and online investment. The method we use in this PkM activity is to provide education to participants regarding illegal online loan products and illegal online investments based on the assessment of the Financial Services Authority (OJK). The purpose of this PkM activity is to provide education regarding illegal online loan products and illegal online investments based on the assessment of the Financial Services Authority (OJK) so that they are more careful in choosing online loan services and online investments. The object of this PkM activity is the Women Farmers Group "Melati Jaya" Sukamenanti Baru Village, Kedaton District, Bandar Lampung City.